PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PROBLEM BASED LEARNING PADA MATERI PENINGGALAN SEJARAH BERCORAK HINDU BUDDHA DI JAWA TIMUR KELAS IV SDN TAROKAN 3 - Tryas Ainun Niza; Karimatus Saidah; Wahid , Wahid Ibnu Zaman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on the observation results, the learning process taking place in grade IV of SDN Tarokan 3 is still conventional, dominated by lecture methods and the use of textbooks with minimal illustrations or supporting visual elements. This condition has an impact on low student interest in learning, lack of active participation during learning, and difficulty in understanding the subject matter. This is also reflected in student learning outcome data which shows that 70% of students obtained scores below the Learning Objective Completion Criteria (KKTP). This study used the Research and Development (R&D) method with the ADDIE development model, which includes five main stages: Analysis, Design, Development, Implementation, and Evaluation. The results showed that the media obtained a validity level of 92% from media experts and 94% from material experts, which is included in the very valid category. In a limited trial involving 10 students, student responses to the media reached 90% which is included in the very good category, while teacher responses to the practicality of the media reached 86% which is included in the very practical category. The results of the students' pre-test in the limited trial showed an average of 47.3, increasing to 86 in the post-test. In a large-scale trial involving 31 students, student responses to the media reached 93%, which is categorized as very good, with an average pre-test score of 45 which increased to 81.6 in the post-test. The results of the Paired Sample t-Test statistical test in both trials showed a significance value of 0.001 < 0.05, indicating a significant difference between the pre-test and post-test scores. This indicates that the use of interactive multimedia based on Problem Based Learning (PBL) is effective in supporting the achievement of learning objectives.